THE URGENCY OF GEOGRAPHICAL INDICATION AS A LEGAL PROTECTION INSTRUMENT TOWARD TRADITIONAL KNOWLEDGE IN INDONESIA - Pulung Widhi Hari Hananto; Rahandy Rizki Prananda (LAW REFORM, 2019)
Traditional knowledge products characterized by geographical conditions are economically and spiritually valuable assets for the people of the area. Potential misleading of geographical indication goods requires a legal instrument that provides protection. Geographical Indication (GI) is one of the instruments of intellectual wealth that has its own characteristics. This study aims to examine the regulations of GeograpicaI Indication in the national and international levels, the implications of geographical indications for stakeholders and the ideal form of setting geographical indications in Indonesia. This study uses normative juridical methods and comparative studies. The results of the study show that the GI’s regulation applied in Indonesia adheres to a system of merging with brand regulation. The implications of GI’s registration bring a comprehensive impact on the economy and the legitimacy of traditional knowledge. After reviewing the comparison of the protection of geographical indications in Ethiopia and Jamaica, the authors recommend to separate the arrangements for geographical indications with brands (sui generis)